The JCI gets a facelift - Savla, Ushma; Hawley, John B. (The Journal of Clinical Investigation, 2004)
A redesigned JCI makes its first appearance: a newly designed logo, a revised layout, more color, and creative use of fonts combine to make the journal an even better read.